"We Are All Chávez": Charisma as an Embodied Experience. (January 2017) - Michelutti, Lucia
The current chaotic post-Chávez political and economic scenario affords a little certainty: Chávez is still very present in the everyday life of contemporary Venezuelans. Chávez as a martyr, as the second Bolívar, as a saint, as a spirit, is becoming part of the religious and social life of a great number of people. Despite being dead, he continues to shape Venezuelan revolutionary selves. An examination of Chávez's legacy through the lens of divine kinship provides important clues to understanding how charisma is embodied in people and things and circulates through networks of kinship (and fictive kinship) from gods, spirits, and ancestors to democratically appointed leaders and their ordinary followers. El caos que permea el panorama político y económico post-Chávez ofrece cierta certeza: Chávez todavía está muy presente en la vida cotidiana de los venezolanos. Chávez se está convirtiendo en parte de la vida religiosa y social de un gran número de personas: Chávez como mártir, como el segundo Bolívar, como santo, como espíritu. A pesar de que está muerto, Chávez sigue moldeando la personalidad revolucionaria venezolana. Un examen del legado de Chávez a través del prisma del parentesco divino nos ofrece claves importantes para entender cómo el carisma se encarna en la gente y en los objetos y circula a través de redes de parentesco (y parentesco ficticio) de los dioses, espíritus y ancestros a los líderes elegidos democráticamente y sus seguidores.